High coverage of the complete mitochondrial genome of the rare Gray's beaked whale (Mesoplodon grayi) using Illumina next generation sequencing. (2nd January 2016) - Thompson, Kirsten F.; Patel, Selina; Williams, Liam; Tsai, Peter; Constantine, Rochelle; Baker, C. Scott; Millar, Craig D.
Abstract: Using an Illumina platform, we shot-gun sequenced the complete mitochondrial genome of Gray's beaked whale ( Mesoplodon grayi ) to an average coverage of 152X. We performed a de novo assembly using SOAPdenovo2 and determined the total mitogenome length to be 16, 347 bp. The nucleotide composition was asymmetric (33.3% A, 24.6% C, 12.6% G, 29.5% T) with an overall GC content of 37.2%. The gene organization was similar to that of other cetaceans with 13 protein-coding genes, 2 rRNAs (12S and 16S), 22 predicted tRNAs and 1 control region or D-loop. We found no evidence of heteroplasmy or nuclear copies of mitochondrial DNA in this individual. Beaked whales within the genus Mesoplodon are rarely seen at sea and their basic biology is poorly understood. These data will contribute to resolving the phylogeography and population ecology of this speciose group.